Al-Shabaab, Social Identity Group, Human (In)Security, and Counterterrorism. (2nd September 2017) - Kfir, Isaac
ABSTRACT: This article examines the link between human security, social identity, and al-Shabaab . The first section explores how social identity group theory can help explain al-Shabaab 's recruitment. The second part focuses on the counterterrorism campaign against al-Shabaab, which involves decapitation, aggressive peacekeeping through a proxy in the shape of the African Union Mission in Somalia, and the role of a domestic de-radicalization program. The article concludes that al-Shabaab 's allure is in decline and the group is facing internal turmoil, which makes its overtures toward the Islamic State of Iraq and the Levant very dangerous, as al-Shabaab could act as an effective conduit between the Arabian Peninsula and Africa.